2022
DOI: 10.1002/dep2.191
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentologic and stratigraphic criteria to distinguish between basin‐floor and slope mudstones: Implications for the delivery of mud to deep‐water environments

Abstract: Deep-water mudstones overlying basin-floor and slope sandstone-prone deposits are often interpreted as hemipelagic drapes deposited during sand starvation periods. However, mud transport and depositional processes, and resulting facies and architecture of mudstones in deep-water environments, remain poorly understood. This study documents the sedimentology and stratigraphy of basinfloor and slope mudstones intercalated with sandstone-prone deposits of the Laingsburg depocentre (Karoo Basin, South Africa). Sedi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 134 publications
0
9
0
Order By: Relevance
“…This way, FA1 (thick and very thick turbidites) may represent periods of relative sea‐level fall (lowstand and early transgression) and intensified remobilization of shallow‐marine deposits into slope area. In turn, FA2 (thin and medium turbidite mudstones) may represent periods of relative sea‐level rise (highstand) and reduced intensity of redeposition into the slope (for discussion on sea‐level control on sediment transfer to slope area, see, for example, Deik et al ., 2021; Boulesteix et al ., 2022; Brooks et al ., 2022, and references therein). Indeed, the FA2 mudstone bed packages show relatively high degree of bioturbation intensity, which can be interpreted to represent periods of significantly reduced sediment input (Boulesteix et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way, FA1 (thick and very thick turbidites) may represent periods of relative sea‐level fall (lowstand and early transgression) and intensified remobilization of shallow‐marine deposits into slope area. In turn, FA2 (thin and medium turbidite mudstones) may represent periods of relative sea‐level rise (highstand) and reduced intensity of redeposition into the slope (for discussion on sea‐level control on sediment transfer to slope area, see, for example, Deik et al ., 2021; Boulesteix et al ., 2022; Brooks et al ., 2022, and references therein). Indeed, the FA2 mudstone bed packages show relatively high degree of bioturbation intensity, which can be interpreted to represent periods of significantly reduced sediment input (Boulesteix et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, FA2 (thin and medium turbidite mudstones) may represent periods of relative sea‐level rise (highstand) and reduced intensity of redeposition into the slope (for discussion on sea‐level control on sediment transfer to slope area, see, for example, Deik et al ., 2021; Boulesteix et al ., 2022; Brooks et al ., 2022, and references therein). Indeed, the FA2 mudstone bed packages show relatively high degree of bioturbation intensity, which can be interpreted to represent periods of significantly reduced sediment input (Boulesteix et al ., 2022). Avulsions between delta lobes on the shelf or high‐frequency climatic changes (humid‐to‐arid) which control the delivery from fluvio‐deltaic system to slope (see, for example, Nakajima et al ., 2009) could be considered as the cause of changes in intensity of sediment input.…”
Section: Discussionmentioning
confidence: 99%
“…Here, background sedimentation refers to hemipelagic settling, and thin dilute sediment gravity flow deposits not visible to the naked eye in outcrop (Boulesteix et al, 2019(Boulesteix et al, , 2020(Boulesteix et al, , 2022. These accumulations of thin beds are interpreted as the product of flowstripping of the dilute upper parts of channelised turbidity currents into the overbank areas (Piper and Normark, 1983;Peakall et al, 2000;Keevil et al, 2006;Kane et al, 2007;Kane and Hodgson, 2011;Hansen et al, 2017a).…”
Section: Fa1: Overbank Depositsmentioning
confidence: 99%
“…Facies Tu4 is composed of the final terms of the Bouma sequence [Te and, less commonly, Td (Bouma, 1962)]. However, recent microscopic studies revealed that bedded deep-water mudstones may have deposited within a slightly more energetic environment than previously considered (Boulesteix et al, 2019(Boulesteix et al, , 2020(Boulesteix et al, , 2022. Facies Tu4 is interpreted to be mainly deposited by suspension fallout of low-density turbidity flows.…”
Section: Facies Description and Depositional Modelmentioning
confidence: 99%